The CRDS spectrum of acetylene near 1.73 µm. (September 2019) - Lyulin, Oleg; Vasilchenko, Semen; Mondelain, Didier; Campargue, Alain
Highlights: High sensitivity absorption spectrum of acetylene is recorded by CRDS near 1.73 µm. The number of assigned lines are 2620 and 250 for 12 C2 H2 and 12 C 13 CH2, respectively. The assigned 12 C2 H2 lines belong to 53 bands which are mostly newly reported. Spectroscopic parameters and Herman–Wallis coefficients are derived. A recommended empirical line list is provided for each band. Abstract: The high-resolution absorption spectrum of acetylene has been recorded at room temperature by high sensitivity cavity ring down spectroscopy (CRDS) in the 5693–5882 cm –1 region. The noise level of the recordings corresponds to a typical minimum detectable absorption, α min, below 10 -10  cm −1 . The positions and intensities of about 4000 lines were determined and analyzed together with about 3900 lines left unassigned in a previous CRDS study in the 5850–6340 cm −1 region. In total, about 2620 12 C2 H2 and 250 12 C 13 CH2 absorption lines are assigned in the present work, most of them being newly reported. The 12 C2 H2 lines belong to 53 bands and include 24 bands newly identified or improved in the region of the previous study. Altogether, 107 bands in the entire 5693–6340 cm −1 while the HITRAN database provides line parameters of only nine 12 C2 H2 bands in the same region. The lines of 12 C 13 CH2 in normal abundance (2.2%) belong to eight bands whose intensities are reported for the first time. Spectroscopic parameters of the upper vibrational levels were derived from standard band-by-band fits of the line positions (typical rms values of the (obs.-calc.) deviations are better than 0.002 cm –1 ). The vibrational transition dipole moment squared and Herman–Wallis coefficients of each band were derived from a fit of the measured intensity values. A recommended line list is provided for the bands newly assigned with positions calculated using empirical spectroscopic parameters of the lower and upper energy vibrational levels and intensities computed using the derived Herman–Wallis coefficients. As a result, the constructed line list includes a total of 4471 transitions belonging to 53 bands of 12 C2 H2 and 8 bands of 12 C 13 CH2 . This list of acetylene transitions above 5693 cm −1 extends to lower energy and completes our empirical spectroscopic database for acetylene in the 5850–9415 cm −1 range. Graphical abstract: Image, graphical abstract